Implementation of Bipolar Adjective Pairs in Analysis of Urban Acoustic Environments - Suhanek, Mia; Đurek, Ivan (Promet - Traffic&Transportation, 2016)
Four different acoustic environments with different loudness levels and spectral distributions were recorded and reproduced to two groups of listeners - control group and experimental group. The questionnaire used in this research relies on the semantic differential method implemented by defining adjective pairs of opposite meaning where each pair describes a sound characteristic for a particular acoustic environment. In analyzing the results, psychological research methodology was used in order to determine statistically significant bipolar adjectives that can appropriately evaluate some given acoustic environment and thus serve as a starting point for a questionnaire and methodology standardization in soundscape research.